Analysis of Students' Critical Thinking Skills in Learning Mathematics as Seen in The Face of Mathematics Anxiety - Tandaria Tandaria; Nur Fahri Tadjuddin; Nursyam Anaguna (Department of Mathematics, Universitas Negeri Padang (UNP), 2025)
The problems found in SMP Negeri 4 Majene are low critical thinking skills, excessive mathematical anxiety of students, students often feel heart palpitations and cold sweats. The purpose of this study is to analyze students' critical thinking skills in mathematics learning in terms of mathematical anxiety. The type of research used is descriptive qualitative research. The subjects of this study were 26 students of class VII. A of SMP Negeri 4 Majene consisting of 17 female students and 9 male students. Then, 9 subjects were selected who had high, medium, and low mathematical anxiety categories using purposive sampling techniques. The instruments used were a mathematical anxiety questionnaire, a test of students' critical thinking abilities, and interview guidelines. This study shows that students with low mathematical anxiety categories are better than students with medium and high mathematical anxiety categories. So, it can be concluded that students with low mathematical anxiety have higher critical thinking abilities than students with moderate levels of mathematical anxiety, and students with moderate levels of mathematical anxiety have higher critical thinking abilities than students with high levels of mathematical anxiety.